Design and experimental evaluation of robust motion synchronization control for multivehicle system without velocity measurements. (17th September 2018) - Zhu, Bo; Zhang, Qingrui; Liu, Hugh H.T.
Summary: This paper investigates the robust motion synchronization problem of a class of multivehicle systems suffering from input disturbances but without velocity measurements. We first evaluate a velocity estimator–based scheme and show the performance limitation of the velocity estimator. We then develop a robust distributed control solution, which includes a passivity filter to inject damping into the system and to yield an output‐feedback stabilizer and a novel continuous disturbance estimator (DE) to achieve disturbance compensation. The solution has three attractive features: (i) both the DE and stabilizer are continuous and have the lowest orders; (ii) the DE can be designed in either the time domain or the frequency domain; (iii) by introducing an ingenious parameter mapping for the DE, it is easy to tune a single parameter to render the steady‐state synchronization and tracking errors sufficiently small. The solution is finally implemented on an experimental platform consisting of four desktop three‐degrees‐of‐freedom helicopters. The results of five control scenarios demonstrate that the platform suffers from severe input disturbances, and that different levels of control accuracy can easily be obtained by tuning the DE parameter.